Quality assurance in the aerospace industry : implementation of AS 9100 Quality Management Standard at an SME - Leonard, Corli (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Industrial Engineering))--University of Stellenbosch, 2011.